Literature Study on the Appointment of Acting Regional Heads from Active Indonesian National Army (TNI) Elements in Regional Autonomy Perspective - Tanjung, Febriasty; Hernadi Affandi; Inna Junaenah (KRTHA BHAYANGKARA, 2025)
This research is a literature study that analyzes the construction of regional autonomy perspectives in the appointment of Acting Regional Heads from the active Indonesian National Army (TNI) based on various academic studies. with various studies among academics. The appointment of acting regional heads from the military raises fundamental questions regarding its consistency with the principles of regional autonomy, merit systems, and local democracy. The main focus of this research is to examine: This research is a literature study that analyzes the construction of regional autonomy perspectives in the appointment of Acting Regional Heads from the active Indonesian National Army (TNI) based on various academic studies. with various studies among academics. The appointment of acting regional heads from the military raises fundamental questions regarding its consistency with the principles of regional autonomy, merit systems, and local democracy. The main focus of this research is to examine: First, How is the construction of regional autonomy perspectives in various studies regarding the appointment of Acting Regional Heads from active TNI elements before the enactment of Permendagri No.4 of 2023? Second, What is the regulatory basis that can be corrected for the appointment of Acting Regional Heads from active TNI elements in the perspective of regional autonomy?. This research uses normative juridical methods and uses secondary data from library materials. The approaches used in this research are legislative approach and conceptual approach. This research concludes: First, the dominance of the perspective stating that the practice of appointing Acting Regional Heads from among the active TNI tends to conflict with local democracy. Second, a more assertive regulatory reformulation is needed in limiting the appointment of Acting Regional Heads from the active TNI and strengthening mechanisms of transparency, accountability, and DPRD participation in the selection process.